Meta‐Omics Analysis Reveals Global Distribution of Toxic Pseudo‐nitzschia and Enhanced Neurotoxin Production Under Climate Warming - Dong Xu; Zhuonan Wang; Georgina L. Brennan; Yuqiu Wei; Guanchao Zheng; Qingshan Luan; Xintong Huang; Yanmin Sun; Jia Yang; Xiaowen Zhang; Ke Sun; Xiao Fan; et al. (Global Change Biology, 2025)
The harmful diatom Pseudo‐nitzschia produces the neurotoxin domoic acid (DA), threatening human health and seafood safety in a changing climate. However, global patterns of Pseudo‐nitzschia abundance and the responses of DA production to underlying environmental drivers remain poorly understood, hindering accurate projections of their responses to environmental change. Using global meta‐omics data from Tara Oceans, alongside field survey data from the Chinese coasts and the Southern Ocean, we present the first evidence that four of the most toxic species— Pseudo‐nitzschia multiseries , Pseudo‐nitzschia multistriata , Pseudo‐nitzschia delicatissima , and Pseudo‐nitzschia pungens —are prevalent not only in coastal ecosystems but also in open ocean environments, spanning from pole to pole. We identify rising temperatures are recognized as a key driver of Pseudo‐nitzschia 's spatial distribution, DA production, and biosynthetic metabolism. Global models suggest that by 2100, under the SSP2‐4.5 climate scenario, the abundance of P. multiseries will increase by approximately 75.4%, while toxin production will be even more significantly enhanced, rising by up to 200.4%. This study significantly expands the known global distribution of these neurotoxin‐producing diatoms and predicts their increasing prevalence and toxicity under future global changes.